THE INFLUENCE OF DEMOCRATIC LEADERSHIP STYLE ON TEACHER PERFORMANCE IN KUTTAB & PPQ AN-NUBUWWAH SUKABUMI - Samsul Aripin Pahruroji; Mulyawan Safwandy Nugraha (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This study aims to explore the effect of democratic leadership style on teacher performance in Kuttab & PPQ An-Nubuwwah Sukabumi. A quantitative approach was used in this study using data collection methods through questionnaires which were distributed to teachers as the research sample. The results of the study show that the democratic leadership style has a significant positive effect on teacher performance. Democratic leadership style allows teachers to involve students in the learning process, encourages active involvement, and builds strong relationships between teachers and students. In the context of Islamic educational institutions, the democratic leadership style has proven effective in increasing student motivation and learning outcomes.